2018
DOI: 10.1111/fwb.13124
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dependence and functional implications of macrophyte–phytoplankton allelopathic interactions

Abstract: Invasive plant species such as Ludwigia hexapetala might have a competitive advantage if they produce allelopathically active compounds against primary producers. Both phytoplankton and plant community structure may be affected due to different, species‐specific sensitivity to allelochemicals. Moreover, such allelopathic interactions could vary over the year depending on (i) the plant's phenological stage and (ii) the abilities of the native macrophytes to suppress—or the non‐native macrophytes to stimulate—th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 58 publications
1
28
0
1
Order By: Relevance
“…The inhibitory potential of allelopathy is complex, and different groups of chemicals can be involved such as phenolic compounds, terpenoids, flavonoids, alkaloids, amino acids, steroids, and carbohydrates (Al‐Samarai et al., 2018). It can be due to the congenital effects of plant containment in soluble substances in water and to biotic and the fluctuations of abiotic parameters, such as climatic conditions (Petrussa et al., 2013), the presence of herbivores and/or pathogens (Gatti et al., 2014; Silva, Overbeck, & Soares, 2014) and stage in the life history of the plant (Lombardo, Mjelde, Källqvist, & Brettum, 2013; Santonja, Le Rouzic, & Thiébaut, 2018; Thiébaut et al., 2018). In recent data, it was reported that the inhibitory activity may be attributed to the accumulation of glucosinolate in the plant parts, especially the leaves (Al‐Samarai et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory potential of allelopathy is complex, and different groups of chemicals can be involved such as phenolic compounds, terpenoids, flavonoids, alkaloids, amino acids, steroids, and carbohydrates (Al‐Samarai et al., 2018). It can be due to the congenital effects of plant containment in soluble substances in water and to biotic and the fluctuations of abiotic parameters, such as climatic conditions (Petrussa et al., 2013), the presence of herbivores and/or pathogens (Gatti et al., 2014; Silva, Overbeck, & Soares, 2014) and stage in the life history of the plant (Lombardo, Mjelde, Källqvist, & Brettum, 2013; Santonja, Le Rouzic, & Thiébaut, 2018; Thiébaut et al., 2018). In recent data, it was reported that the inhibitory activity may be attributed to the accumulation of glucosinolate in the plant parts, especially the leaves (Al‐Samarai et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in contrast with the trend reported by Nektarios et al () with the use of P. halepensis needle leachates, we observed a clear increasing inhibitory effect related to VOC according to the evolution of needle physiological stage (green needle < senescent needle < needle litter). Since the allelochemicals released in leachates belong usually to phenolics (Fernandez et al, ; Santonja, Le Rouzic, et al, ), the water solubility, and rapid leaching of these compounds, could explain the decreasing allelopathic potentialities along needle physiological stages (Chomel et al, ; Hashoum et al, ). Santonja, Baldy, et al () and Chomel et al () reported that 40% and 80% of phenolics disappeared after 2 and 6 months of P. halepensis needle litter decomposition, respectively, supporting the findings of Nektarios et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Seed germination percentage was calculated as [(number of germinated seeds)/(number of sown seeds)] × 100 (Bousquet-Mélou et al, 2005;Gavinet et al, 2019;Santonja, Le Rouzic, et al, 2018). Regarding seedling growth, root length (mm) was measured for each individual 5 days after germination (Fernandez et al, 2006(Fernandez et al, , 2013Hashoum et al, 2017).…”
Section: Allelopathic Bioassay With Pinus Halepensis Vocmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed germination and seedling performance are the main life stages usually affected by allelochemicals (i.e. phenolics or terpenoids), and frequent negative allelopathic effects are inhibition of seed germination (Herranz et al, 2006;Fernandez et al, 2013), delay of seed germination (Fernandez et al, 2013;Hashoum et al, 2017) and inhibition of seedling growth (Santonja et al, 2018;Gavinet et al, 2019). Several plant physiological processes such as photosynthesis, nutrient uptake, cell division or elongation can be influenced by the allelochemicals released (Chou, 1999;Inderjit and Duke, 2003).…”
Section: Introductionmentioning
confidence: 99%